2012
DOI: 10.15835/nbha4016648
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Polyphenols Content and Antimicrobial Activity of Several Native Pteridophytes of Romania

Abstract: The aim of this paper was to test the antioxidant activity, polyphenols content and antimicrobial activity of crude extracts obtained from leaves of pteridophyte species commonly found in Romania

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Therefore, inhibition of the phorbol dibutyrate receptors may lead to an inhibition of contractility and may contribute to the effect of DF in this study. Earlier studies reported significant antioxidant activity of DF possibly because of the presence of several phenolic compounds (Sekendar Ali et al 2012;Soare et al 2012). These support the compounds detected in these studies, which had varied components of phenol groups.…”
Section: Biological Effects Of Identified Compounds In D Filix-massupporting
confidence: 80%
“…Therefore, inhibition of the phorbol dibutyrate receptors may lead to an inhibition of contractility and may contribute to the effect of DF in this study. Earlier studies reported significant antioxidant activity of DF possibly because of the presence of several phenolic compounds (Sekendar Ali et al 2012;Soare et al 2012). These support the compounds detected in these studies, which had varied components of phenol groups.…”
Section: Biological Effects Of Identified Compounds In D Filix-massupporting
confidence: 80%
“…Furthermore, the consumption of these may magnify a disease since the bacteria becomes stronger to medication. The use of natural extracts to interfere with bacterial adhesion has recently gained substantial attention [20][21][22]. Microbial pigments are a promising alternative to other natural extracts from vegetables because they pose no seasonal production problems and show high productivity [23].…”
Section: Introductionmentioning
confidence: 99%
“…7 Ayurvedic medical system suggested the medicinal uses of fern plants for the treatment of several diseases too. 8 The rhizome of Osmunda regalis has been traditionally employed in Spain, mainly for the treatment of bone fractures, joint disorders and rheumatic and arthritic pain. 9 Many indigenous ferns have been used commonly as folk medicines in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…18 Phenolic compounds are common metabolites in plants which have biological activities such as anti-inflammatory, anti-cancer and antioxidant. 19 Several extracts from ferns exhibited remarkable antioxidant capacity, comparable with vitamin C. 8 Flavonoids and other phenolic compounds have been demonstrated to be potent antioxidants. Hence, one of the functional properties of ferns that are pertinent to human health is their antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%